Taxonomy, productivity potential and edodibility of the soils under different land use systems in selected watersheds of the western ghats region in Kerala - Anup V M (Department of soil Science and Agricultural Chemistry, College of Agriculture, 2004)
Four subwatersheds namely Kallupalamthode, Ayithithode, Thuruthithode and Attingalthode were selected in Aruvikkara watershed of Nedumangad Taluk, Thiruvananthapuram District, Kerala, for assessing the erodibility of the soils, productivity potential, fertility capability classification and soil classification. Four catenary sequences were identified in each watershed based on land use and degree of degradation. The land use prevalent in the different physiographic positions were forest (eucalyptus plantation) in the crest, agricultural land (coconut based mixed cropping system) in the upper sideslope and footslope and rubber plantation in the lower sideslope sites. The erodibility indices such as dispersion ratio, erosion ratio and erosion index showed high values in all the study sites indicating that these soils are highly susceptible to erosion. The study area is characterized by steep slope, which when coupled with high rainfall, is very much prone to runoff and soil loss of varying degrees. In Kallupalamthode, Ayithithode and Thuruthithode watersheds, more than 80 percent of the area had already been brought under soil conservation measures, whereas in Attingalthode watershed, no soil conservation measures have been adopted so far. But the soils in all the four watersheds showed high values of erodibility indices, revealing their susceptibility to erosion. High erodibility indices in the conserved watersheds may be attributed to the fact that soil conservation measures had been adopted only recently and as such the impact of the protective measures in controlling soil erosion was not observable. From the general productivity potential of the area, an attempt was made to arrive at the productivity class for the soils in which specific crops are grown. Coconut, banana and tapioca are being grown in the upper sideslope and footslope sites in all the catenary sequences. Based on the ratings for coconut, it is observed that the soils in the footslope in Kallupalamthode watershed, upper sideslope and footslope in Ayithithode watershed and footslope in Thuruthithode watershed have high potential, while the soils in the upper sideslope and footslope sites in Attingalthode watershed had medium productivity potential. The soils in the upper sideslope site in Kallupalamthode watershed had only low potential for coconut. For tapioca, the footslope site in Kallupalamthode watershed, upper sideslope and footslope in Ayithithode, Thuruthithode and Attingalthode watersheds had high productivity potential. In the case of banana, the upper sideslope site had low potential and footslope site medium potential in Kallupalamthode watershed, high in Ayithithode watershed, high in the footslope and medium in the upper sideslope in Thuruthithode watershed and medium in the respective sites in Attingalthode watershed. In the lower sideslope sites in all the catenary sequences where rubber is grown in the study area, it is observed that these sites have high productivity potential for rubber. Based on the physical and chemical parameters, all the soils in the study area were grouped into FCC units. The grouping showed that all the soils were either loamy or clayey in the surface and substrata and were favourable for the cultivation of coconut, tapioca, banana, arecanut, rubber, mango, jack and pepper. The adverse effect of more than 35 percent gravels was more pronounced in the loamy than in clayey soils. Although the soils had relatively low CEC, it is observed that with suitable management, this limitation could be overcome. Soils of the study area had been classified as per the comprehensive soil classification system, USDA. It is observed that only two soil series occur in the study area, namely Palode and Nedumangad series, which are placed under the order Ultisols. In the crest site all the soils come under the great group kanhaplohumults, while in the lower physiographic positions either under kanhaplohumults, plinthohumults or plinthustults. Palode series occur in the upper physiographic positions namely crest and upper sideslope, while Nedumangad series occur on the lower physiographic positions. The major problem identified in the watershed areas is soil erosion. The mechanical measures adopted in the study area for conserving soils are restricted to contour bunding and bench terracing, in agricultural lands and rubber plantations respectively. Since the study area is characterized by steep slope, and high rainfall, the possibility of adopting diversion type terraces may be explored. Practice of contour cultivation in steep areas is also desirable for controlling soil erosion. Most of the natural forests in the crest sites have been cleared for raising eucalyptus plantation. This disturbance on the land surface had resulted in making the soils highly vulnerable to erosion, and subsequent land degradation. In such situations, construction of ‘catch water drains’ for the safe conduct of water from the summit without soil loss is recommended. Construction of grass waterways is also a suitable suggestion for the study area. Instead of adopting a single conservation measure, it would be better to think of a suitable combination of mechanical and vegetative measures on a watershed basis, so that soil loss could be minimized.